Characterization of reference genes for RT-qPCR in the desert moss Syntrichia caninervis in response to abiotic stress and desiccation/rehydration - Li, Xiaoshuang; Zhang, Daoyuan; Li, Haiyan; Gao, Bei; Yang, Honglan; Zhang, Yuanming; Wood, Andrew J. (Frontiers in Plant Science, 2015)
Syntrichia caninervis is the dominant bryophyte of the biological soil crusts found in the Gurbantunggut desert. The extreme desert environment is characterized by prolonged drought, temperature extremes, high radiation and frequent cycles of hydration and dehydration. S. caninervis is an ideal organism for the identification and characterization of genes related to abiotic stress tolerance. RT-qPCR expression analysis is a powerful analytical technique that requires the use of stable reference genes. Using available S. caninervis transcriptome data, we selected 15 candidate reference genes and analyzed their relative expression stabilities in S. caninervis gametophores exposed to a range of abiotic stresses or a hydration-desiccation-rehydration cycle. The programs geNorm, NormFinder, and RefFinder were used to assess and rank the expression stability of the 15 candidate genes. The stability ranking results of reference genes under each specific experimental condition showed high consistency using different algorithms. For abiotic stress treatments, the combination of two genes (α-TUB2 and CDPK) were sufficient for accurate normalization. For the hydration-desiccation-rehydration process, the combination of two genes (α-TUB1 and CDPK) were sufficient for accurate normalization. 18S was among the least stable genes in all of the experimental sets and was unsuitable as reference gene in S. caninervis. This is the first systematic investigation and comparison of reference gene selection for RT-qPCR work in S. caninervis. This research will facilitate gene expression studies in S. caninervis, related moss species from the Syntrichia complex and other mosses.